Clinical outcomes of CyberKnife stereotactic radiosurgery for elderly patients with presumed primary stage I lung cancer - Wang, Zhen (Transl Lung Cancer Res, 2017)
BACKGROUND: In certain situations, especially in the elderly patient population, a tissue diagnosis of a suspected pulmonary neoplasm is not feasible. Often, a definitive treatment such as stereotactic body radiosurgery is recommended, rather than active surveillance. The aim of this study is to evaluate the efficacy and tolerability of stereotactic body radiotherapy (SBRT) for elderly patients with presumed primary stage I lung cancer without pathological tissue confirmation. METHODS: We performed a retrospective analysis of 25 elderly patients (≥75 years) with presumed primary stage I lung cancer treated with SBRT from 2009–2015. The primary end point was local control (LC); secondary end points were survival and toxicity. RESULTS: The median follow-up (FU) was 36.0 months (range, 4 to 84 months). The 1-year LC rate was 100%, 3-year LC rate was 78.8%, and 5-year LC rate was 65.7%. The median progression-free survival (PFS) time was 48.0 months (95% CI: 31.2–64.8). The 1-, 3-, and 5-year overall survival (OS) rates were 96.0%, 70.2%, and 50.7%, respectively. The 1-, 3-, and 5-year cancer-specific survival (CSS) rates were 100%, 81.3%, and 67.0%, respectively. No grade 4 or higher toxicity was encountered. CONCLUSIONS: SBRT is safe and effective treatment for patients with presumed primary stage I lung cancer where obtaining pathological confirmation of malignancy is challenging.